2019
DOI: 10.1002/ps.5591
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and herbicidal activity of novel pyrazole aromatic ketone analogs as HPPD inhibitor

Abstract: BACKGROUND 4‐Hydroxyphenylpyruvate dioxygenase (HPPD, EC 1.13.11.27) has been a good target for herbicide discovery. In order to discover novel HPPD herbicides, a series of pyrazole aromatic ketone analogs were designed and synthesized. RESULTS The 25 pyrazole aromatic ketone analogs synthesized were tested for herbicidal activity and compounds A1, A3, A4, A17, A20 and A25 displayed excellent herbicidal activity against Chenopodium serotinum, Stellaria media and Brassica juncea at 37.5 g ha−1. In addition, com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
54
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 73 publications
(61 citation statements)
references
References 54 publications
0
54
0
Order By: Relevance
“…Soybean, canola, cotton, corn, rice, and wheat were selected and underwent crop safety testing 26–29 . The commercial herbicide mesotrione was selected as a positive control.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Soybean, canola, cotton, corn, rice, and wheat were selected and underwent crop safety testing 26–29 . The commercial herbicide mesotrione was selected as a positive control.…”
Section: Methodsmentioning
confidence: 99%
“…Soybean, canola, cotton, corn, rice, and wheat were selected and underwent crop safety testing. [26][27][28][29] The commercial herbicide mesotrione was selected as a positive control. Of the tested crops, proximately 20 seeds (bud rate ≥ 85%) were sown in composite nutrient soil at a depth of 2 cm and grown at a temperature of 15 to 30°C in a glasshouse.…”
Section: Crop Selectivitymentioning
confidence: 99%
See 1 more Smart Citation
“…Many new kinds of pesticides with high efficiency, low toxicity and low residue have been developed. Heterocyclic derivatives received important attention due to their various biological activities [ 1 , 2 , 3 , 4 , 5 , 6 ]. Among these compounds, 1,2,4-oxadiazole heterocyclic derivatives, which contain nitrogen and oxygen atoms, displayed diverse activities, such as insecticidal activity [ 7 , 8 , 9 ], antifungal activity [ 10 , 11 ], herbicidal activity [ 12 ], anti-inflammatory [ 13 ], hypotensive [ 14 ] and other physiological activity.…”
Section: Introductionmentioning
confidence: 99%
“…In recent reference, her group 17 built a modelling of the P. capsici cellulose synthase 3. In our previous work [18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35] , many bioactive compounds were designed and synthesised. In this paper, based on the structure of seven commercialised CAA fungicides, we found that they have similar structural fragments: amide bond, para-substituted phenyl, 3,4-dialkyloxy substituted phenyl.…”
Section: Introductionmentioning
confidence: 99%